Animal models of chronic traumatic encephalopathy - Kelly M McAteer; Renee J Turner; Frances Corrigan (Concussion)
Repeated head impacts have been suggested to be associated with the development of the neurodegenerative disorder, chronic traumatic encephalopathy (CTE). CTE is characterized by the accumulation o...